2020
DOI: 10.1002/jcb.29668
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of tachykinins and their receptors

Abstract: Tachykinins (TKs) are a family of neuropeptides mainly expressed by neuronal and non-neuronal cell types, especially immune cells. Expression of TKs receptors on immune cell surfaces, their involvement in immune-related disorders, and therefore, understanding their immunomodulatory roles have become of particular interest to researchers. In fact, the precise understanding of TKs intervention in the immune system would help to design novel therapeutic approaches for patients suffering from immune disorders. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Several studies have recently demonstrated that SP induces a series of signaling pathways through NK1R that mediate cellular excitability in several human tumor cells. It has important roles in forming and spreading various tumor cells via migration, angiogenesis, and metastasis [11][12][13][14][15][16]. is is important since the prevention of metastasis is a major goal in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently demonstrated that SP induces a series of signaling pathways through NK1R that mediate cellular excitability in several human tumor cells. It has important roles in forming and spreading various tumor cells via migration, angiogenesis, and metastasis [11][12][13][14][15][16]. is is important since the prevention of metastasis is a major goal in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, TAC4 gene products were various in different species. TAC4 in mice and rats can encode one hemokinin mature peptide with 11 amino acid length [ 25 ]. In human, TAC4 encodes for hemokinin-1 (hHK-1), but its sequence is different from its murine counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that tachykinins and their receptors regulate the development, activation, and function of critical immune cells and the immune system. Tachykinins are also involved in immune cell migration, immune cell proliferation, and inflammation regulation with cytokines [ 26 , 27 ]. We analyzed the correlation between expression levels of TACR2 and the content of immune cells and found that expression levels of TACR2 positively correlated with mast cells and negatively correlated with M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%